Isolasi bakteri resisten merkuri pada urin pasien dengan tumpatan amalgam di Puskesmas Tuminting - Bahter, Julia V.F.; Kepel, Billy J.; ., Fatimawali (Universitas Sam Ratulangi, 2016)
Abstract: Metal is very important for human life, albeit, some of them have toxic effects. Mercury is a heavy metal with a high toxicity level. In the field of dentistry, mercury is used as an ingredient of amalgam. The use of amalgam apparently triggers resistant bacteria due to continuous release of mercury since the usage of condensing amalgam in the tooth. This study was aimed to determine whether there were mercury-resistant bacteria in the urine of patients who had amalgam-filling tooth at Puskesmas Tuminting (primary health care) and to identify the types of mercury-resistant bacteria. This was a descriptive exploratory study using urine samples of patients in dental clinic with amalgam fillings minimal for 6 months. The results obtained 30 isolates of mercury-resistant bacteria with 6 genera of bacteria resistant to mercury, as follows: Klebsiella sp, Bacillus sp, Staphylococcus sp, Hafnia sp, Enterobacter sp, and Eubacteria sp. Conclusion: There were mercury-resistant bacteria in the urine of patients with amalgam-filling teeth in the Dental Clinic of Puskesmas Tuminting.Keywords: amalgam, mercury-resistant bacteria Â Abstrak: Logam sangat penting bagi kehidupan manusia. Walaupun demikian beberapa jenis logam memiliki efek toksik, salah satunya ialah merkuri. Merkuri tergolong logam berat dengan tingkat toksisitas yang tinggi. Dalam bidang kedokteran gigi, merkuri digunakan sebagai salah satu bahan campuran amalgam. Penggunaan amalgam ternyata memicu bakteri resisten merkuri dikarenakan pelepasan Hg secara terus menerus sejak dilakukan kondensasi amalgam di dalam mulut. Penelitian ini bertujuan untuk mengetahui apakah terdapat bakteri resisten merkuri dalam urin pasien yang menggunakan amalgam di Puskesmas Tuminting dan untuk mengidentifikasi jenis bakteri resisten merkuri yang ditemukan. Jenis penelitian ialah deskriptif eksploratif. Sampel penelitian ialah urin pasien di Poli Gigi dengan tumpatan amalgam minimal 6 bulan. Hasil penelitian menapatkan dari 30 isolat bakteri resisten merkuri terdapat 6 genus bakteri yang resisten terhadap merkuri, yaitu: Klebsiella sp, Bacillus sp, Staphylococcus sp, Hafnia sp, Enterobacter sp, dan Eubacteria sp. Simpulan: Terdapat bakteri resisten merkuri dalam urin pasien dengan tumpatan amalgam merkuri di Poli Gigi Puskesmas Tuminting.Kata kunci: amalgam, bakteri resisten merkuri